Estudio bioestratigráfico y paleoambiental de la Formación Río Turbio (Eoceno Medio a Superior) en el sudoeste de Patagonia (Argentina) basado en quistes de dinoflagelados - González Estebenet, María Sol (2015)
During the middle and late Eocene the Austral Basin, in southern Patagonia (Argentina), was fl ooded by an AtlanticOcean transgression, which was responsible for the deposition of the upper member of the Río Turbio Formation. We haveanalyzed the dinofl agellate cyst assemblages from this stratigraphic section in order to provide a biostratigraphic frameworkand reconstruct the paleogeographic and paleoceanographic conditions in this area. Dinofl agellate cyst events recorded werecompared and interpreted based taking into account other records recognized for the South Pacifi c Ocean. The comparisonallowed us to suggest an age between 45.5 Ma (mid-Lutetian) and 33.5 Ma (Priabonian) for the upper member of the RioTurbio Formation. We recognized three zones of dinofl agellate cysts. Zone I presents an alternating dominance betweenEnneadocysta dictyostila, Defl andrea antarctica and Vozzhennikovia apertura indicating two sea level rises. Zone II isdominated by V. apertura suggesting high trophic levels and cool waters in a shallow-marine coastal environment. The lowerpart of the Zone III shows a high abundance of Turbiosphaera fi losa with different morphotypes, which may correspond tophysicochemical changes in the water column. The uppermost part of the Zone III is characterized by Protoperidinaceae andtypical forms of T. fi losa suggesting an oceanic environment infl uenced by upwelling processes. Zones I and II are defi nedby the dominance of middle Eocene endemic-Antarctic assemblage, while Zone III shows a signifi cant replacement of thesetaxa by cosmopolitan species. This turnover seems to be forced by the deepening of the Southern Atlantic Ocean gatewaysand the changes in the ocean circulation patterns.